PERAN PENDIDIKAN GIZI DALAM MENINGKATKAN PENGETAHUAN, SIKAP DAN PERILAKU GIZI SEIMBANG PADA REMAJA DI SMA YASMU KECAMATAN MANYAR KABUPATEN GRESIK - Dian Agnesia (President University, 2019)
Obesity is a problem that is quite high in Indonesian society, but is most often ignored. Obesity is a global epidemic problem that must be dealt with seriously. The Riskesdas (2013) data stated that the proportion of adolescents (16-18 years) with excess body weight was 7.3%, with obesity category 1.6%, and the remaining 5.7% in the category of overweight, the incidence of obesity experiencing an increasing trend until 2018. The Global School Health Survey (2015) data found that the cause of the high number of obesity is due to the diet of adolescents who often skip breakfast (65.2%), consuming less fiber from vegetables and fruits (93.6%), often consume junk foods that are high in sodium (75.7%) and lack of physical activity (42.5%). This community service activity aims to increase adolescent knowledge of food and the importance of applying a healthy and active lifestyle in daily life. Knowledge will influence a person's attitude and behavior in applying balanced nutrition in their daily lives. Balanced nutrition behavior is expected to reduce nutritional problems among adolescents and this will be seen from the daily diet of teenagers.In this community service activity participants were found to be obese nutritional status (4%), overweight or overweight (21%) and thin (12%). Participant’s knowledge increased with the category of good knowledge by 28%, increasing to 38% after Nutrition Education. The participant's attitude related to the Balanced Nutrition Guidelines was mostly in the less category (58%), while the participant's behavior in applying the 4 pillars of Balanced Nutrition was still mainly related to maintaining an ideal body weight (58%) and active and exercising lifestyle (83%).